2016
DOI: 10.3390/ijms17101630
|View full text |Cite
|
Sign up to set email alerts
|

Direct LAMP Assay without Prior DNA Purification for Sex Determination of Papaya

Abstract: Papaya (Carica papaya L.) is an economically important tropical fruit tree with hermaphrodite, male and female sex types. Hermaphroditic plants are the major type used for papaya production because their fruits have more commercial advantages than those of female plants. Sex determination of the seedlings, or during the early growth stages, is very important for the papaya seedling industry. Thus far, the only method for determining the sex type of a papaya at the seedling stage has been DNA analysis. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
4
0
3
Order By: Relevance
“…Therefore, isothermal amplification can be used to measure a small number of RNAs. Isothermal amplification has been used for virus detection, SNP detection, sex detection, and RNA amplification [57,58,59]. Examples of isothermal amplification are loop-mediated isothermal amplification (LAMP) [60], rolling circle amplification (RCA) [61], transcription-mediated amplification (TMA) [62], nucleic acid sequence-based amplification (NASBA) [62], strand displacement amplification (SDA) [63], isothermal multiple displacement amplification (IMDA) [64], helicase-dependent amplification (HAD) [65], single primer isothermal amplification (SPIA) [66], and SmartAmp [58,67].…”
Section: Isothermal Amplificationmentioning
confidence: 99%
“…Therefore, isothermal amplification can be used to measure a small number of RNAs. Isothermal amplification has been used for virus detection, SNP detection, sex detection, and RNA amplification [57,58,59]. Examples of isothermal amplification are loop-mediated isothermal amplification (LAMP) [60], rolling circle amplification (RCA) [61], transcription-mediated amplification (TMA) [62], nucleic acid sequence-based amplification (NASBA) [62], strand displacement amplification (SDA) [63], isothermal multiple displacement amplification (IMDA) [64], helicase-dependent amplification (HAD) [65], single primer isothermal amplification (SPIA) [66], and SmartAmp [58,67].…”
Section: Isothermal Amplificationmentioning
confidence: 99%
“…Researchers also attempted to completely avoid nucleic acid isolation and instead apply the sample directly into the isothermal amplification mix. This has been demonstrated for plants using the example of papaya [ 15 ] and for the fecal indicator bacteria E. coli and E. faecalis [ 16 ]. The authors concluded that the elevated temperature of 63 °C could lead to increased cell permeability, allowing direct amplification of the target DNA.…”
Section: Case Study: Towards Implementing a Field-applicable Workflowmentioning
confidence: 99%
“…LAMP has been used in many field studies as a molecular technique, such as the detection of malaria parasites (Plasmodium falciparum; Paris et al, 2007), the detection of Fusarium graminearum, the cause of Downy Mildew in wheat (Triticum aestivum L.), and also for the identification of human DNA (Kanchanaphum, 2018). Moreover, LAMP has been used to determine the sex of various plants, including papaya (Tsai et al, 2016), asparagus (Shiobara et al, 2011), and spinach (Fujita et al, 2017). In raptor species, sex identification based on LAMP also has been developed (Centeno-Cuadros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%